Pengaruh Human Relation Islami Terhadap Kepuasan Kerja Pada Hotel Natama - Umar Ma’ruf Manik; maya sari (CERED Indonesia Institute, 2023)
The goal of Islamic human relations on job satisfaction at hotels is to create a balanced and harmonious work environment for hotel employees. This can be achieved by implementing Islamic values in human resource management practices, such as fairness, equality and mutual respect. This study uses a quantitative approach. The population and sample are 40 respondents, namely the employees of Hotel Natama Padangsidempuan. The data source used in this research is primary data obtained by distributing questionnaires to respondents. Data analysis techniques in this study were data quality testing, classic assumption testing, multiple linear regression analysis and hypothesis testing using SPSS software version 25. The results of this study indicated that Islamic human relations had an effect on Islamic job satisfaction. From the results of the Islamic human relations analysis test, it has a positive effect on Islamic job satisfaction. This is evidenced by the results obtained based on hypothesis testing, and a significance value of 64.3% and the remaining 35.7% is influenced by other variables not examined in this study .